Annual Lateral Organic Carbon Exchange Between Salt Marsh and Adjacent Water: A Case Study of East Headland Marshes at the Yangtze Estuary - Yuan, Yiquan; Li, Xiuzhen; Xie, Zuolun; Xue, Liming; Yang, Bin; Zhao, Wenzhen; Craft, Christopher B. (Frontiers in Marine Science, 2022)
Blue carbon (C) ecosystems (mangroves, salt marshes, and seagrass beds) sequester high amounts of C, which can be respired back into the atmosphere, buried for long periods, or exported to adjacent ecosystems by tides. The lateral exchange of C between a salt marsh and adjacent water is a key factor that determines whether a salt marsh is a C source (i.e., outwelling) or sink in an estuary. We measured salinity, particulate organic carbon (POC), and dissolved organic carbon (DOC) seasonally over eight tidal cycles in a tidal creek at the Chongming Dongtan wetland from July 2017 to April 2018 to determine whether the marsh was a source or sink for estuarine C. POC and DOC fluxes were significantly correlated in the four seasons driven by water fluxes, but the concentration of DOC and POC were positively correlated only in autumn and winter. DOC and POC concentrations were the highest in autumn (3.54 mg/L and 4.19 mg/L, respectively) and the lowest in winter and spring (1.87 mg/L and 1.51 mg/L, respectively). The tidal creek system in different seasons showed organic carbon (OC) export, and the organic carbon fluxes during tidal cycles ranged from –12.65 to 4.04 g C/m2. The intensity showed significant seasonal differences, with the highest in summer, the second in autumn, and the lowest in spring. In different seasons, organic carbon fluxes during spring tides were significantly higher than that during neap tides. Due to the tidal asymmetry of the Yangtze River estuary and the relatively young stage, the salt marshes in the study area acted as a strong lateral carbon source.